Explosion Flame and Pressure Characteristics of Nonstick Coal Dust and the Inhibition of Explosion Suppressants - Tianqi Liu; Ruiheng Jia; Xiaoting Dong; Xuan Zhao; Weiye Tian; Zhixin Cai; Ning Wang (Journal of Chemistry)
Nonstick coal is widely distributed in the world and is an important resource for human beings. The explosion characteristics and explosion suppression of nonstick coal dust are increasingly concerning. In this paper, the flame and pressure characteristics of a nonstick coal dust explosion are studied, and the suppression effect of SiO2, KCl, and NH4H2PO4 on the explosion is analyzed. It is concluded that the maximum propagation distance of a nonstick coal dust explosion flame is 0.59 m, the maximum pressure is 0.63 MPa, and the maximum pressure rise rate is 40.79 MPa/s. The explosion suppression effect of SiO2 is worse than that of KCl, but the inhibition effect of NH4H2PO4 is the best among the three kinds of explosion suppressants. When the mass percentage of NH4H2PO4 dust mixed with coal dust is 70%, the coal dust explosion is completely suppressed. It absorbs a certain amount of heat to promote the chemical reaction, which plays a certain role in controlling the explosion process, and its explosion suppression mechanism includes both physical and chemical explosion suppression.